(untitled) (Journal of the College of Basic Education, 2022)
There is no doubt that any real study in the poetry of Muhammad Mahdi Al-Jawahiry (1900-1997) requires the investigation of a century charged with political, social and intellectual fluctuations, which was almost completely reflected in his poetry as he moves between jobs and countries, using his high poetic ability and his ability to adapt the language in an artistic manner, reviewing his treasury Lexical and voluntarily creative imagination in E.